(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article presents the didactic principles, methodological approaches and principles of planning the educational process for the effective organization of the teaching of mathematics in primary grades. The article analyzes the role of lesson structure, teaching methods, use of game and interactive activities in the formation of students’ knowledge, qualifications and skills in mathematics lessons. In addition, methodological recommendations are given to improve the effectiveness of lessons as a result of the use of individual approaches to teaching, differential tasks, visual aids, modern pedagogical technologies. The results of the research serve to improve the quality of mathematics teaching in the primary education system and the development of students’ mathematical thinking.